Produção de videoaulas para EaD : contribuições para o diálogo com os educandos - Mazzeu, Ian Rittmeister (Universidade Federal de São Carlos, 2012)
This work discusses the production of video lessons made for E-Learning courses. It is written according to what Paulo Freire calls a problem-posing concept of education, on which dialogue is the key element for the consolidation of the educational process. The approach onto the video lesson object is done through two consonant ways: the educational processes on which it is inserted and the audiovisual language over which it is build up. Therefore, regarding the educational processes, the main concepts discussed in here are the problem-posing education and the banking education, as conceived by Freire, plus the dialogue constituents, as stated by Bakhtin. On the audiovisual language matters, it is of great concern the problem of the spectator identification the interlocutor of a video lesson. Thus, in order to debate it, this work will present its main components, such as the plan, the montage and the sound. After that, it will examine how their different arrangements may incur in what Ismail Xavier describes as the opacity and the transparency of the audiovisual speech. There is, as well, a revision over video lessons on a historical perspective, concerning the Brazilian context, where some initiatives are detached, such as Telecurso and the movies produced by the Instituto Nacional de Cinema INCE. Lastly, there are some results concerning a Case Study of a video lesson produced for a class of the Pedagogy Course of the Federal University of São Carlos UFSCar, which is an elearning course.
Keywords: Comunicação; Linguagem - recursos audiovisuais; Educação a distância; Videoaulas; E-learning; Audiovisual; Video lessons; Dialogue; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO